A polyketide synthase gene cluster required for pathogenicity of Pseudocercospora fijiensis on banana - Elizabeth Thomas (Public Library of Science (PLoS), 2021)
Pseudocercospora fijiensis is the causal agent of the highly destructive black Sigatoka disease of banana. Previous research has focused on polyketide synthase gene clusters in the fungus, given the importance of polyketide pathways in related plant pathogenic fungi. A time course study of expression of the previously identified PKS7-1, PKS8-2, and PKS10-2 gene clusters showed high expression of all three PKS genes and the associated clustered genes in infected banana plants from 2 weeks post-inoculation through 9 weeks. Engineered transformants silenced for PKS8-2 and PKS10-2 were developed and tested for pathogenicity. Inoculation of banana plants with silencing transformants for PKS10-2 showed significant reduction in disease symptoms and severity that correlated with the degree of silencing in the conidia used for inoculation, supporting a critical role for PKS10-2 in disease development. Unlike PKS10-2, a clear role for PKS8-2 could not be determined. Two of four PKS8-2 silencing transformants showed reduced disease development, but disease did not correlate with the degree of PKS8-2 silencing in the transformants. Overall, the degree of silencing obtained for the PKS8-2 transformants was less than that obtained for the PKS10-2 transformants, which may have limited the utility of the silencing strategy to identify a role for PKS8-2 in disease. Orthologous PKS10-2 clusters had previously been identified in the related banana pathogens Pseudocercospora musae and Pseudocercospora eumusae. Genome analysis identified orthologous gene clusters to that of PKS10-2 in the newly sequenced genomes of Pseudocercospora fuligena and Pseudocercospora cruenta, pathogens of tomato and cowpea, respectively. Our results support an important role for the PKS10-2 polyketide pathway in pathogenicity of Pseudocercospora fijiensis, and suggest a possible role for this pathway in disease development by other Pseudocercospora species.